Evaluation of Placement and Protection Programs of Indonesian Migrant Worker (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to evaluate the placement and protection programs of Indonesian migrant worker that they run by the Ministry of Manpower and The National Agency of Placement and Protection of Indonesian Migrant Worker. This research is done by observation, interview and documentation with Discrepancy Evaluation Model method. The method is to evaluate design, installation, process and the Implementation of the Placement and Protection programs of Indonesian migrant worker against the Employment Placement Private Company to provide Indonesian Migrant Workers services licensed by the Ministry of Manpower and placement permits from The National Agency for Placement and Protection of Indonesian Migran Workers, the role of local government on one-stop integrated service, the role of labor attaches in Indonesian embassy from the Ministry of Manpower and supervision of The Nasional Agency for Placement and Protection of Indonesian Migrant Worker. The conclusion of this study indicates that there is a gap in discrepancy at 16.01% from the target to be achieved.